2020
DOI: 10.1063/1.5128595
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the understanding of the glycerol to lactic acid reaction mechanism over AuPt/TiO2 under alkaline conditions

Abstract: The oxidation of glycerol under alkaline conditions in the presence of a heterogeneous catalyst can be tailored to the formation of lactic acid; an important commodity chemical. Despite recent advances in this area, the mechanism for its formation is still a subject of contention. In this study, we use a model 1 wt.% AuPt/TiO2 catalyst to probe this mechanism through conducting a series of isotopic labelling experiments with 1,3-13 C glycerol. Optimisation of the reaction conditions was first conducted to ensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…For example, the Cannizzaro reaction explain the absence of DHA in alkaline media and the formation of Lactate. [35,36] Other well-known equilibria in carbon hydrates chemistry is that between glucose and fructose [37] then we have proposed the equivalent equilibria between glyceraldehyde and DHA. Unfortunately, these reactions are several times not considered in many papers in the field of electrocatalysis, where the authors claim the J o u r n a l P r e -p r o o f electrochemical production of substances that several times are formed just by pure chemical steps.…”
Section: Discussionmentioning
confidence: 98%
“…For example, the Cannizzaro reaction explain the absence of DHA in alkaline media and the formation of Lactate. [35,36] Other well-known equilibria in carbon hydrates chemistry is that between glucose and fructose [37] then we have proposed the equivalent equilibria between glyceraldehyde and DHA. Unfortunately, these reactions are several times not considered in many papers in the field of electrocatalysis, where the authors claim the J o u r n a l P r e -p r o o f electrochemical production of substances that several times are formed just by pure chemical steps.…”
Section: Discussionmentioning
confidence: 98%
“…Selective oxidation of glycerol has been demonstrated to be thermodynamically more favorable for C–H bond activation under mild reaction conditions (e.g., lower operating temperature and alkali concentration), which greatly reduces energy consumption ( Shen et al, 2010 ; Lakshmanan et al, 2013 ; Tao et al, 2017 ; Evans et al, 2020 ; Tao et al, 2020 ; Torres et al, 2021 ). Furthermore, low reaction temperature can also significantly inhibit C–C bond cleavage by alkalis, thus good selectivity of C 3 products.…”
Section: Catalytic Conversion Of Glycerol To Lamentioning
confidence: 99%
“…Furthermore, low reaction temperature can also significantly inhibit C–C bond cleavage by alkalis, thus good selectivity of C 3 products. Selective oxidation of glycerol to LA is generally carried out with the promotion of various noble metal and some non-noble metal catalysts (e.g., Au, Pt, Pd, and polyoxometalate ) ( Shen et al, 2010 ; Lakshmanan et al, 2013 ; Xu et al, 2013 ; Cho et al, 2014 ; Purushothaman et al, 2014 ; Zhang et al, 2016a ; Zhang et al, 2016b ; Arcanjo et al, 2017 ; Tao et al, 2017 ; Zhang et al, 2017 ; Douthwaite et al, 2020 ; Evans et al, 2020 ; Tao et al, 2020 ; Torres et al, 2021 ; Wang et al, 2021 ). In the first important advances, Shen et al (2010) reported that the bimetallic Au–Pt catalysts exhibit excellent performances with a high yield of 86% in the presence of alkali and O 2 at 90°C.…”
Section: Catalytic Conversion Of Glycerol To Lamentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction is commonly described in the literature under basic conditions, mainly due to the fact that alkaline media accelerates the reaction, improves the selectivity to C3 products, and prevents deactivation [183]. Recent advances in the employment of noble metals as active phases, especially Au and Pt, are focused on selective oxidation base-free and room condition reactions [29,[184][185][186][187]. In this line, support properties may be key to achieving this objective through metal particle sintering prevention [188], as well as the establishment of metal synergies with superficial acid-base centers [189].…”
Section: Glycerol Selective Oxidationmentioning
confidence: 99%